Development of Crohn´s disease in a patient with ankylosing spondylitis and essential thrombocythemia following etanercept therapy - A case report and the review of the literature - Milić, Biljana; Ilić, Tatjana; Popović, Milica; Savić, Aleksandar; Jocić, Tatiana; Petrović, Lada (Vojnosanitetski pregled, 2021)
Introduction. The development of inflammatory bowel disease during the treatment with tumor necrosis factor-α inhibitors is seen in patients with ankylosing spondylitis. Crohn´s disease is the mainly developing form, and etanercept is the most frequently associated agent. Although thrombocytosis in patients with ankylosing spondylitis and inflammatory bowel diseases is often seen due to chronic inflammation, iron deficiency anemia or drug administration, presence of essential thrombocythemia is not common. To our knowledge, there is no published data of coexistence of these three diseases in one patient. Case report. We reported a 35-year-patient with simultaneous presentation of ankylosing spondylitis and essential thrombocythemia. Due to hepatotoxicity of initial treatment with sulfasalazine and metotrexate, tumor necrosis factor-α inhibitor (etanercept) was introduced. Both diseases were well controlled until Crohn´s disease emerged. Two years after switching from etanercept to adalimumab all three coexisting diseases were in remission. Conclusion. Treatment with tumor necrosis factor-α inhibitors significantly improved clinical outcome of patients with chronic inflammatory diseases. However, the appearance of adverse effects may cause a discontinuation or change of a drug. The existence of comorbidities additionally complicates the treatment of such patients.